Optimization tolerancing of surface in flexible parts and assembly: Influence Coefficient Method with shape defects - Atik, Hafsa; Chahbouni, Mouhssine; Amegouz, Driss; Boutahari, Said (International Journal of Engineering and Technology, 2018)
Generally, a mechanical product must fulfill particular functions in accordance with the specification provided by the customer. A designer must find a solution with lower cost to answer the functional requirements. After the design stage, come the prototyping of the parts, but in case of the large structures of automotive and aeronautical parts, this step is impossible because of the large real dimension as well as the behavior of this type of parts during the positioning and during the assembly of all the mechanism.The aim of this article is to show the influence of geometrical shape differences in the assembly of flexible components in order to optimize the tolerancing of surface in flexible parts and assembly. first a presentation of the tolerance of deformable mechanisms through the illustration of the general problem, then we propose a new approach which takes into account shape defects based on the Influence Coeficient Method, after that we compare between a case study without takes into account shape defects and another one but this time taking into account shape defects always based on the Influence Coefficient Method.